Sustainable Infrastructure Development: A Case Study of Kalaotoa Village, Pasilambena District, Selayar Islands Regency - Nur Sandi Marsuni (Pustaka Digital Indonesia, 2024)
This qualitative descriptive research investigates the infrastructure development strategies employed in Kalaotoa Village, Pasilambena District, Selayar Islands Regency. Through observations, interviews, and documentation studies, the study unveils a systematic approach to infrastructure development aimed at enhancing various aspects of community life, including Education, Social, Economic, Health, and Religious domains. The research findings underscore a holistic perspective, emphasizing not only economic progress but also social welfare improvement. By focusing on sectors like Education, Health, and Religion, the village demonstrates a commitment to comprehensive community development. The study provides valuable insights into how infrastructure development strategies at the village level can significantly impact society's well-being.